Experiences of Teachers in Upland Schools: A Phenomenological Study (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
This research study used a descriptive qualitative phenomenological research design which provides a narrative context based on personal experiences. The participants of the study were four teachers, teaching in highland elementary campuses for more than a year. The data were contextualized from participants in depth statement according to the open-ended questionnaire that has been provided during the evaluation. Learners were intellectually challenged, needed to be guided by parents or siblings using supplementary activities given in the modules. With a lack of technological intervention professional teachers in upland areas are having difficulty to monitor the improvement of their learners. Most of the learners cannot fully comply on their academic activities. Learners don’t understand the module, they rely on their elder siblings. Moreover, the common struggles of the teachers is the risk in travelling due to the topographical settings. Common disadvantage teaching in upland and remote campuses was the unsuited learning curriculum for the learners. Provided learning guide were not culture based, which means, learners are having difficulty in understanding which translate to haphazard learning development. Participants stated that their students are struggling in self-learning method, considering that most of the parents of these learners are illiterate. Therefore, it suggests developing a mode of learning delivery based on the learner’s capacity to learn and improve. In spite of all the struggles, there was enjoyment. Most of them perceived that the common advantage in upland schools is having a small class size. Thus, teachers can focus in teaching.